Comparison between thermal pasteurization and high pressure processing of bovine skim milk in relation to denaturation and immunogenicity of native milk proteins. (June 2018) - Bogahawaththa, Dimuthu; Buckow, Roman; Chandrapala, Jayani; Vasiljevic, Todor
Abstract: High pressure processing (HPP), conducted at 400, 500 or 600 MPa for 15 min at 30 °C, of raw skim milk was studied in comparison to high-temperature short-time (HTST) pasteurization (72 °C for 15 s), considering protein denaturation and immunogenicity. HTST pasteurization least impacted denaturation of native proteins leading to mostly unchanged milk immunogenicity. HPP resulted in denaturation of whey proteins, mostly β-lactoglobulin (BLG) and immunoglobulin G (IgG), and disturbed structure of the casein micelle. HPP at 600 MPa caused protein aggregation, involving mainly BLG and κ-casein, through thiol disulphide interactions. α-Lactalbumin (ALA) was least denatured. The balance between expression of T helper (Th)1 and Th2 type cytokines, which is believed to regulate adverse immune response, was initially shifted toward Th1 with increasing high pressure, then the immunogenic capacity of milk proteins diminished at 600 MPa. This could be related to exposure of T cell-specific linear epitopes followed by unfolding of protein structure firstly and masking of them by protein aggregation subsequently with increasing high pressure. Industrial relevance: HPP of raw milk has been well studied as an alternative process for conventional thermal pasteurization, based on inactivation of microorganisms and extension of shelf life. However, HPP can denature native milk proteins leading to altered immunogenicity. Three recommended HPP conditions and a commercial HPP method were assessed in comparison to HTST pasteurization considering impact on denaturation of milk proteins and milk immunogenicity. Scientific findings of the current study would guide the industry to identify HPP conditions that not only achieve the required level of microbial inactivation and shelf life, but also to establish desired levels of native properties of milk and milk immunogenicity. Highlights: High pressure methods recommended for milk processing affected native proteins. β-Lactoglobulin and immunoglobulin G were greatly denatured at or above 400 MPa. Milk immunogenicity altered significantly with increasing pressure (400–600 MPa). Altered milk immunogenicity was associated with the level of protein denaturation.